LINKING FINANCIAL LITERACY AND ENTREPRENEURIAL CHARACTERISTICS - Melvin S. Sarsale (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Linking financial literacy and entrepreneurial characteristics remain unexplored in the Philippine setting. This paper tried to address this gap by investigating the correlation between financial literacy and entrepreneurial characteristics. This paper also examined differences and correlations of gender and senior high school (SHS) strand on these factors. This study employed descriptive-correlational design and gathered the needed data from 157 students enrolled in a Philippine university using an adopted survey instrument. The findings revealed a significant positive correlation between financial literacy and entrepreneurial characteristics, except for cash management when linked to innovativeness and tolerance for ambiguity, and no significant correlation of these factors when associated with gender and SHS strand, except for gender and risk-taking propensity. The findings also revealed no significant difference in gender and SHS strand in all variables, except for risk-taking propensity between males and females. The results suggested that innovation and tolerance for ambiguity posed no relevance in managing cash. The findings also implied the influence of gender in risk-taking propensity and on how males and females viewed risks differently. The results further confronted the relevance of the accountancy, business, and management (ABM) strand in promoting financial literacy and entrepreneurship much better than non-ABM as expected.